WORKSHOP GOOGLE GEMINI UNTUK MEMBUAT ARTIKEL DENGAN TEKNIK SEO BAGI ANGGOTA KOPERASI MAHASISWA UIN K.H. ABDURRAHMAN WAHID PEKALONGAN - Pujiono, Imam Prayogo; Prayogi, Arditya; Firdausi, Muh Izzat (Dharma Pengabdian Perguruan Tinggi (DEPATI), 2024)
The rapid development of Information Technology has had a major impact on various aspects of life, especially in education and business. Information technology is a type of technology that helps humans process and obtain information; an example is Artificial Intelligence (AI). Google Gemini is Google's most advanced AI and can be used for various things, such as creating articles that comply with SEO (Search Engine Optimization) techniques. UIN K.H. Abdurrahman Wahid Pekalongan Student Cooperative (KOPMA UIN Gusdur) is a cooperative that was founded on November 10 1998. To realize its vision, KOPMA UIN Gusdur held training activities for its members regarding creating articles using SEO techniques so that the managed website gets many visitors. Community Service (PKM) activities were carried out in response to this need by holding a Google Gemini workshop to create articles using SEO techniques. The workshop's main objective is to improve the ability of KOPMA UIN Gusdur members to create articles using SEO techniques with Google Gemini to produce interesting articles that can appear on the first page of search engines. The workshop was carried out using presentation methods and direct practice via the website www.gemini.google.com and was attended by 24 participants from members of KOPMA UIN Gusdur. Pre-Test and Post-Test are given to workshop participants to assess their initial and final abilities regarding the material provided. The result of this activity is an increase in participants' ability to use Google Gemini to create articles using SEO techniques. The increase in participants' abilities can be seen from the results of the Pre-Test and Post-Test questionnaires where overall, from the 6 questions given, there was an average increase of 9.33 participants or 68.28% of participants who previously answered that they could not use Google Gemini to do a work, but then he could use it after following the workshop. The advice given to workshop participants was to be able to utilize Google Gemini to support their business development.